Missed opportunities? The development of human welfare in Western Europe, 1913-1950 - Daniel Gallardo Albarrań (European Historical Economics Society (EHES), 2017)
Income per capita suggests that the period 1913-1950 is one of missed opportunities for improving living standards in Europe. However, life in Europe during these years improved significantly, as citizens began experiencing dramatic declines in mortality, working time and inequality thanks to (among others) the spread of modern medicine and the introduction of the 8-hour working day. To measure the contribution of these aspects to broader welfare, I apply a new utility-based framework that, contrary to previous composite indices such as the Human Development Index, allows for a welfare analysis directly comparable to GDP across countries and time. The results using the new measure shows that income per capita underestimates welfare growth significantly (up to five percent annually). Moreover, with this indicator cross-country differences in living standards are much larger and more persistent than other composite indices of well-being imply. These findings call for a reappraisal of the evolution of living standards during the period 1913-1950 and, more generally, of the measurement of multi-dimensional welfare in historical contexts.
Keywords: I10; I3; N30; D63; O53; 330; Living Standards; welfare; well-being; twentieth-century; life expectancy; leisure